"He Helped Me in Discovering Myself." Rethinking and Exploring Sexual and Gender Identity in Trans-Inclusive Relationships. Issue 2 (17th February 2023) - Siboni, Laura; Prunas, Antonio; Anzani, Annalisa
Abstract: This qualitative study explores the effects of being in a relationship with a transgender or non-binary (TGNB) person on an individual's sexual and/or gender identity. To this aim, the responses of 107 partners of TGNB individuals to the following open-ended question were collected: " What effect, if any, has having a relationship with a transgender person had on your gender and/or sexual identity? ." Through thematic analysis, 4 overarching themes emerged from the participants' responses: 1) No reason to change; 2) Exploration and changes; 3) New perspective; and 4) Negative effects and confusion. Overall, this study suggests that being in a relationship with a TGNB person may prompt a reflection on the concept of sexual and gender identity, and an exploration of one's own identity, which is usually experienced as positive, but may also be a source of distress for the individual and/or the couple. Also, in many other cases, the relationship has been observed to have no effect on the partner's identity, due to a number of reasons. These findings constitute a relevant addition to the understanding of couple's dynamics in trans-including couples.